Individual and social determinants of COVID-19 vaccine hesitancy and uptake in Northwest Syria - Orwa Al-Abdulla; Maher Alaref; Agneta Kallström; Jussi Kauhanen (BMC, 2024)
Abstract Introduction The COVID-19 outbreak devastated the fragmented health system in Syria, a war-torn country, and exaggerated the demands for humanitarian assistance. COVID-19 vaccination was rolled out in Northwest Syria, an area out of government control, in May 2021. However, vaccine acceptance rates are still minimal, which is reflected in the meager percentage of vaccinated people. The study aims to investigate the effectiveness of the humanitarian actors' plans to address the COVID-19 vaccine hesitancy and conclude practical strategies for boosting vaccine uptake in Northwest Syria. Methods and materials Two questionnaires were developed to collect data from humanitarian organizations involved in the COVID-19 vaccination campaign and people from northwest Syria. Data analysis was performed using SPSS 22 data analysis program. Results According to the findings, 55.5% of people refused the COVID-19 vaccine. The results showed a knowledge gap and lack of evidence regarding humanitarian actors' strategies to address the vaccine's low uptake. Besides, it was found that doctors and medical workers were reliable sources of information about the vaccine. However, they were not systematically engaged in community mobilization and risk communication to promote people's perspectives on the vaccine. Conclusion Risk communication and community engagement programs were not significantly associated with increasing the COVID-19 acceptance rate. Humanitarian actors must reconsider their strategies to address vaccine hesitancy in Northwest Syria. These strategies should engage medical professionals through dialogue sessions on the realities of the pandemic and vaccine development mechanism based on a compelling and evidence-based approach.